Prenatal Midtrimester Fetal Long Bone Measurements and the Prediction of Small-for-Gestational-Age Fetuses at Term - Speer, Paul D.; Canavan, Timothy; Simhan, Hyagriv N.; Hill, Lyndon M. (American Journal of Perinatology, 2014)
Objective To determine if the length of fetal long bones (LB) at mid-trimester ultrasound is predictive of small-for-gestational-age (SGA) newborns at term delivery.Methods Retrospective evaluation of 6,781 women between 18 and 24 weeks' gestation at Magee-Womens Hospital (MWH). Gestational age (GA) was confirmed by first- or second-trimester ultrasound and patient's last menstrual period. Data were accrued from the institutional database at MWH. LB measurements were normalized to GA at the time of the ultrasound. The ratio was correlated with the probability of delivering an SGA newborn at term.Results In all, 583 women were identified with an SGA newborn (8.6%). LB-to-GA ratios were associated with the probability of delivering an SGA newborn at term (p < 0.001). There was no single LB that proved to be superior in predicting an SGA newborn.Conclusion There is a significant association between LB-to-GA ratio at midtrimester and the probability of SGA at term.
Keywords: femur length; ultrasound; small for gestational age